Carbon-based molecular devices: Fano effects controlled by the molecule length and the gate voltage. Issue 34 (16th August 2016) - Yang, X. F.; Kuang, Y. W.; Liu, Y. S.; Zhang, D. B.; Shao, Z. G.; Yu, H. L.; Hong, X. K.; Feng, J. F.; Chen, X. S.; Wang, X. F.
Abstract : Left panel: Schematic plots of the carbon-based devices under the gate voltage. The arrows represent the direction of electric fields. Right panel: The linear conductance G σ and spin-dependent Seebeck coefficient S σ versus the gate voltage. Abstract : Fano effect is an important quantum phenomenon in mesoscopic systems, which arises from an interference between the localized state and the extended state. Here we observe an obvious Fano effect near the Fermi level in an all-carbon molecular device consisting of an acene molecule sandwiched between two zigzag graphene nanoribbon (ZGNR) electrodes. By increasing the length of the molecule, an extended state gradually evolves into a localized state. With the aid of the nearby extended state, a Fano effect is achieved. Using a gate voltage, we can easily tune the Fano effect induced by the single-transmission channel. When the spin degree of freedom is involved, the all-carbon device can show a half-metallic property with positive or negative 100% spin polarization at the Fermi level under the gate voltage; meanwhile the spin thermoelectric effect can also be enhanced.